2017
DOI: 10.32674/jis.v7i1.250
|View full text |Cite
|
Sign up to set email alerts
|

But I Don’t Understand You: One Faculty’s Observations of the Challenges Facing International Healthcare Students

Abstract: International students face many challenges when pursuing a degree in higher education. Communication and cultural differences are typically cited as the most challenging aspects of any study abroad program. Students attempting to complete a healthcare program face sometimes insurmountable issues, as communication, cultural differences, and discrimination play a large role in providing quality patient care. This paper is a commentary on my experiences as a faculty member with various international students enr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…Similarly, Moores and Popadiuk (2011) found that more in-depth preparation benefits transitioning students. When the student's awareness about the host culture is augmented, they are more equipped to handle the challenges in the host country (DuBose, 2017;Moores & Popadiuk, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Moores and Popadiuk (2011) found that more in-depth preparation benefits transitioning students. When the student's awareness about the host culture is augmented, they are more equipped to handle the challenges in the host country (DuBose, 2017;Moores & Popadiuk, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…The literature has identified communication, cultural differences, and discrimination as challenges experienced by international students in general and specifically by those studying in the United States. [40][41][42][43] Thus, collaborative experiences should address such challenges to ensure a successful social and academic experience during the time the students stay in the host country. Support from peers, instructors, and the university are key to helping the students adjust during their stay.…”
Section: Global Engagementmentioning
confidence: 99%
“…Visiting students should be trained to be tactful when communicating with faculty members, preceptors, and health care providers so as not to disturb the established hierarchy in a negative way, and to act professionally when providing opinions or questioning authority. 43,60,61 Both cultural and academic differences may potentially lead to hosts forming negative stereotypes about the students prior to, during, or after the experience. This may be because they have general stereotypes or bias about a certain group of students, students' ethnic or religious background, or their respective country of origin.…”
Section: Acculturationmentioning
confidence: 99%
“…face challenges not only because of barriers concerning communication, but also in mitigating cultural differences and discrimination [14]. These students have to adapt to a completely different culture and make a cultural transition [15].…”
Section: Country Of Origin International Studentsmentioning
confidence: 99%